2013
DOI: 10.1097/ta.0b013e3182995c70
|View full text |Cite
|
Sign up to set email alerts
|

Embolization for pediatric blunt splenic injury is an alternative to splenectomy when observation fails

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…Although the role of SAE has been firmly established in adults as a treatment option for those who fail nonoperative management of splenic injury, its utility in the management of pediatric splenic trauma is limited. 27 Upon analysis of a national database, we found that embolization for high-grade splenic injury has equivalent transfusion rates, morbidity, and mortality compared with splenectomy by adjusted analysis.…”
Section: Commentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Although the role of SAE has been firmly established in adults as a treatment option for those who fail nonoperative management of splenic injury, its utility in the management of pediatric splenic trauma is limited. 27 Upon analysis of a national database, we found that embolization for high-grade splenic injury has equivalent transfusion rates, morbidity, and mortality compared with splenectomy by adjusted analysis.…”
Section: Commentsmentioning
confidence: 93%
“…In comparison, smaller studies with 15 or less patients reported no deaths. 2,3 Our study draws from a national database and provides more robust and generalizable estimates of the morbidity and mortality for this procedure.…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations